Artificial Intelligence and the Challenge to Human Literature: Revisiting Borges and Cortázar (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2024)
When the popularity of cinema and the emergence of mass culture shook the foundations of art as it was known and recognized until the early 20th century, Walter Benjamin wrote his essay “The Work of Art in the Age of Its Technological Reproduction” in an attempt to highlight the irreplaceability and authenticity of the artwork embodied in its aura and to confront the challenges posed by the new era. Almost a century later, it seems that we are facing an even greater challenge to the traditional conception of art as an authentic and unique human activity, we are facing literature created by artificial intelligence. And while many reject categorically the possibility that this “humanoid literature” could ever be considered equal to “human literature,” it cannot be denied that artificial intelligence and its creative achievements in the field of literature question the very foundations of human art. Somewhat unexpectedly, writers like Jorge Luis Borges and Julio Cortázar and their conceptions of literature can provide possible answers to the questions of the new era. Their works show that the issue of the author and their biography should be revisited after more than a century of rejection of the 19th-century biographism in literary theory. On the other hand, the theory of reception and the relation between author and reader acquire a new dimension when seen through the lens of these authors’ oeuvre.